History of the establishment of teacher training in Ukraine (the second half of the nineteenth century — in 1939) - Левітас, Фелікс; Дудар, Ольга (Educological discourse, 2013)
The article is devoted the analysis of development of temporal courses for teachers on the different stages of history of Ukraine in period of second halves XIX century — in 1939. In this work are first used publications of researchers of school matter of times of the Russian empire and the unique archived documents of soviet times.